2015
DOI: 10.1016/j.seizure.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a phone app for epilepsy diagnosis in India and Nepal

Abstract: A tool presented as a phone app can be used by non-medical health workers to identify episodes as epileptic or not with good accuracy. It needs to be evaluated more widely but has the potential to play a part in reducing the epilepsy treatment gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Patterson et al 2015 56 In rural areas telemedicine programs started through non-medical health workers to reach out people who cannot access quality epilepsy care due to the shortage of skilled physicians Community health workers visited door-to-door in order to fill up the appbased questionnaire to identify people with Epilepsy. These data were later used to design comprehensive services.…”
Section: Videoconferencing and Teleconsultationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterson et al 2015 56 In rural areas telemedicine programs started through non-medical health workers to reach out people who cannot access quality epilepsy care due to the shortage of skilled physicians Community health workers visited door-to-door in order to fill up the appbased questionnaire to identify people with Epilepsy. These data were later used to design comprehensive services.…”
Section: Videoconferencing and Teleconsultationmentioning
confidence: 99%
“…The current review identified 11 papers reporting the issue of shortage of healthcare service providers. 29,39,[42][43][44][45][46][47][53][54][55][56] 3 papers have highlighted the issue of inadequate health facilities. 29,41,54 These three papers discussed one common thing, which was the lack of skilled and specialized healthcare service providers outside of the mega cities of Nepal.…”
Section: Satellite Phone Patient Data Sharing Portable Computer Andmentioning
confidence: 99%
“…This has been presented as a smartphone application [9] (app) which, in response to a series of questions, generates a probability score of the episodes being epileptic or not. The algorithm underlying the app uses a Bayesian approach and was developed in a Nepalese population [10] and validated in India and Nepal [11]. This app, presented on a tablet computer, can be used easily by computer-naïve NPHWs [12] and, when compared to the diagnosis of a neurologist, can generate similar agreement to that of local doctors studies [11,13]with specificities of 100% and 33%.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm underlying the app uses a Bayesian approach and was developed in a Nepalese population [10] and validated in India and Nepal [11]. This app, presented on a tablet computer, can be used easily by computer-naïve NPHWs [12] and, when compared to the diagnosis of a neurologist, can generate similar agreement to that of local doctors studies [11,13]with specificities of 100% and 33%. More importantly its misdiagnosis rate was 8% compared with 25% for the tool designed in South Asia by Anand et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Dr Brunklaus raises excellent points regarding the potential for misdiagnosis of epilepsy in intellectual disability (ID) and the paucity of rigorously tested screening tools for epilepsy, particularly when it is comorbid with neurodevelopmental features such as ID and autism spectrum disorder. This is a major unmet need, particularly in resource‐poor health‐care settings where app‐based screening tools have been trialed to reduce the treatment gap . We did not propose that the ESQ could be used to diagnose epilepsy; our intention was to screen for signs and symptoms that might suggest a history of seizures.…”
mentioning
confidence: 99%